THE SYNTHESIS OF CHITOSAN POLYMER MEMBRANE/PVA AS AN ECO-FRIENDLY BATTERY FOR ALTERNATIVE ENERGY RESOURCE - Widiarti, Nuni; Sumarni, Woro; Setyaningrum, Lysa (Jurnal Bahan Alam Terbarukan, 2017)
The eco-friendly materials which have not commonly developed as energy storage alternative sources are solid electrolytes. Chitosan is one of the natural polymer potentially used as the material of solid electrolytes. The purpose of this study is to determine the conductivity value of chitosan polymerâs electrolytes-PVA-glutaraldehyde-NH4Br by varying amount of chitosan and ammonium bromide salt (NH4Br). The polymer electrolyte membrane was made using phase inversion method. Electrolyte polymer is made by mixing chitosan, PVA, glutaraldehyde, and NH4Br to become homogenous liquid and then printed it in petri dish. Polymer electrolyte with chitosan variation of 2; 2.4; 2.8 and 3.2 g has highest ionic conductivity of 1.4983 x 10-2 S/cm with the addition of 2.8 g that can be used as the optimum composition. The variations of salt (NH4Br) were 0; 0.2; 0.4; 0.6; 0.8 and 1 g has the highest ionic conductivity in the point of 2.4385 x 10-2 S/cm with the addition of 0.6 g. The characterization result of FTIR shows OH group at the wavenumber of 3362.02Â  cm-1, C-O group at 1740.43 cm-1, and C=N group at 1542.41 cm-1. Synthesized polymer can be used as a battery that has 0.43 V voltage.